URGENSI DESAIN KURIKULUM DALAM UPAYA MEMAJUKAN PENDIDIKAN DI INDONESIA - Herlina, Herlina (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2018)
The problem which often arise is show up the Indonesia has problem seriously, namely moral crisis. Problem by problem that arise become an education to be a good solution. One of it, curriculum straighten with a critical of important something before design of curriculum. So, the important problem of curriculum that relevan to this study is how to design of curriculum development in Indonesia. Even the development is procecing up to this time, but the changing is done to a goodness in a future. A porpuse of this study is understandable how to redesign of curriculum to this study or edocation of this state (Indonesia). The study method that an author is analysis content and documentation. The result of this study is design as an important education to this straighten, that is implementatedable to the Grasroots Rationale of Taba Model.